2019
DOI: 10.1007/s11013-019-09638-5
|View full text |Cite
|
Sign up to set email alerts
|

A Point in the Heart: Concepts of Emotional Distress Among Albanian-Speaking Immigrants in Switzerland

Abstract: Cultural variability regarding concepts of distress for common mental disorders (CMD) has been reported extensively in cultural clinical psychology across the globe. However, little is known about illness narratives in social communities from Southeast Europe. The purpose of this paper is to identify cultural concepts of distress (CCDs) among Albanian-speaking immigrants in Switzerland and to integrate the findings into literature from other parts of the world. Twenty semi-structured qualitative interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 89 publications
2
16
0
2
Order By: Relevance
“…They found that more rigorous studies revealed CCD that clearly dif-fered from Western diagnoses of common mental disorders. Such studies examine people's ways of expressing suffering, their assumptions about causes of distress and possible ways to overcome it, physiological and spiritual meanings attributed to suffering, and the distinction between universal human suffering and mental illness (e.g., Keys, Kaiser, Kohrt, Khoury, & Brewster, 2012;Kohrt & Hruschka, 2010;Shala, Morina, Salis Gross, Maercker, & Heim, 2019).…”
Section: Theoretical and Empirical Foundations For Cultural Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that more rigorous studies revealed CCD that clearly dif-fered from Western diagnoses of common mental disorders. Such studies examine people's ways of expressing suffering, their assumptions about causes of distress and possible ways to overcome it, physiological and spiritual meanings attributed to suffering, and the distinction between universal human suffering and mental illness (e.g., Keys, Kaiser, Kohrt, Khoury, & Brewster, 2012;Kohrt & Hruschka, 2010;Shala, Morina, Salis Gross, Maercker, & Heim, 2019).…”
Section: Theoretical and Empirical Foundations For Cultural Adaptationmentioning
confidence: 99%
“…Another example are findings related to fatalism. An ethnopsychological study showed that Albanian-speaking immigrants in Switzerland understood their suffering as part of normal life, given by god or fate (fati), and something that cannot be cured but has to be borne with endurance (durim) (Shala et al, 2019). Fatalism was also found among Turkish immigrants in Germany (Franz et al, 2007;Reich, Bockel, & Mewes, 2015).…”
Section: Cultural Concepts Of Distressmentioning
confidence: 99%
“…Several studies showed that the cross-cultural setting might be a challenge to provide appropriate mental health care to refugees and asylum seekers for a variety of reasons such as stigma, taboo, trust issues, and a mismatch between Western concepts of diagnosis and treatment and the problems and needs perceived by refugees and asylum seekers [4,40,[65][66][67][68][69][70][71][72]. Moreover, the expression of the perceived problems, idioms of distress, or symptom expression of common mental disorders can vary substantially within and between cultural backgrounds and may decrease the accuracy of diagnostic appraisals and treatment outcome [73][74][75][76]. Therefore, a culturally sensitive treatment approach considering i.a.…”
Section: Barriers To More Frequent Treatment Of Refugees and Asylum Smentioning
confidence: 99%
“…Hassan et al (2005) note that many Syrian refugees attribute obsessive rumination to satanic temptations, using the Arabic word wisswas meaning both the devil and unpleasant recurrent thoughts. Among Albanian migrants in Switzerland, this has been referred to as a "point in the heart" or "Brenge": the beginning of rumination triggered by different causes (Shala et al, 2020). Droždek and Wilson (2007) highlight some more examples from the literature: In the experience of many Salvadoran refugees who report "attaques nervios," a somatic response involving feelings of anxiety, fear, and anger, and calor, an experience of intense heat that extends through one's body.…”
Section: Culturally-informed Responses To Trauma: Attributing Meaningmentioning
confidence: 99%